2018
DOI: 10.1007/978-3-030-01228-1_33
|View full text |Cite
|
Sign up to set email alerts
|

View-Graph Selection Framework for SfM

Abstract: View-graph is an essential input to large-scale structure from motion (SfM) pipelines. Accuracy and efficiency of large-scale SfM is crucially dependent on the input viewgraph. Inconsistent or inaccurate edges can lead to inferior or wrong reconstruction. Most SfM methods remove 'undesirable' images and pairs using several, fixed heuristic criteria, and propose tailor-made solutions to achieve specific reconstruction objectives such as efficiency, accuracy, or disambiguation. In contrast to these disparate sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…However, the completeness and accuracy are still affected compared to using the full set. Shah et al (2018) proposed an optimisation‐based formulation to achieve different reconstruction objectives. The method improves efficiency with a comparable accuracy compared to the full view‐graph.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the completeness and accuracy are still affected compared to using the full set. Shah et al (2018) proposed an optimisation‐based formulation to achieve different reconstruction objectives. The method improves efficiency with a comparable accuracy compared to the full view‐graph.…”
Section: Related Workmentioning
confidence: 99%
“…This redundancy slows methods that are sensitive to the number of images, such as COLMAP (Schonberger & Frahm, 2016). Second, redundancy with an uneven distribution usually occurs with insufficient baselines, which causes more unreliable 3D geometry in triangulation‐based SfM (Michelini & Mayer, 2020; Shah et al, 2018). Finally, an uneven distribution has a negative effect on bundle adjustment (BA) accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these two criteria, the triplet compatibility indicator is formulated as max ( ∠ ( , 3×3 ) , ∠ ( , 180°) ). Finally, we employ a greedy triplet deleting scheme: starting with the triplet with the largest indicator, a triplet is deleted as long as the remaining triplets are still connected and no image is deleted from the photogrammetric block (see Appendix for more details on generating the OMCTS), note that we introduce our triplet selection process in a less sophisticated way and a more grounded graph theory based explanation is given by Shah et al (2018).…”
Section: Generation Of An Optimal Minimum Cover Connected Image Triplmentioning
confidence: 99%
“…This can create problems, if rotations are incorrectly estimated. In addition, many researchers (Wilson and Snavely, 2014;Shah et al, 2018) also found that global methods are sensitive to outliers of relative orientations, since outliers are difficult to detect in global computations.…”
Section: Introductionmentioning
confidence: 99%
“…However, large-scale scenes often contain ambiguous structures caused by repeating or symmetric elements and the reconstruction results in SfM can be collapsed by their false match pairs. Recently, some research [Shah et al 2018;Shen et al 2016] has attempted to use additional prior knowledge to solve this issue and improve the SfM performance. Nontheless, these methods are still too scene dependent and still cannot solve more challenging situations, such as stairwells.…”
Section: Introductionmentioning
confidence: 99%